Phylogenetic analysis of human Chlamydia pneumoniae strains reveals a distinct Australian indigenous clade that predates European exploration of the continent. (December 2015) - Roulis, Eileen; Bachmann, Nathan; Humphrys, Michael; Myers, Garry; Huston, Wilhelmina; Polkinghorne, Adam; Timms, Peter
Abstract Background The obligate intracellular bacteriumChlamydia pneumoniae is a common respiratory pathogen, which has been found in a range of hosts including humans, marsupials and amphibians. Whole genome comparisons of humanC. pneumoniae have previously highlighted a highly conserved nucleotide sequence, with minor but key polymorphisms and additional coding capacity when human and animal strains are compared. Results In this study, we sequenced three Australian humanC. pneumoniae strains, two of which were isolated from patients in remote indigenous communities, and compared them to all availableC. pneumoniae genomes. Our study demonstrated a phylogenetically distinct humanC. pneumoniae clade containing the two indigenous Australian strains, with estimates that the most recent common ancestor of these strains predates the arrival of European settlers to Australia. We describe several polymorphisms characteristic to these strains, some of which are similar in sequence to animalC. pneumoniae strains, as well as evidence to suggest that several recombination events have shaped these distinct strains. Conclusions Our study reveals a greater sequence diversity amongst both human and animalC. pneumoniae strains, and suggests that a wider range of strains may be circulating in the human population than current sampling indicates.